BRST Charge Operator for Generalized Deformed SU(2) Algebra - Loan, Nguyen Thi Ha; Ha, Nguyen Hong (Communications in Physics, 2008)
The BRST Charge plays a prominent role in interaction theory based on the Gauge symmetry group. In this work we find the explicit expression of the BRST charge for Generalized deformed SU(2) algebra.